Three-dimensional dipole momentum analog based on L-shape metasurface - Li, Tianyou; Chen, Yanjie; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Applied Physics Letters)
The achievement of a flat metasurface has realized extraordinary control over light–matter interaction at the nanoscale, enabling widespread use in imaging, holography, and biophotonics. However, three-dimensional metasurfaces with the potential to provide additional light–matter manipulation flexibility attract only little interest. Here, we demonstrate a three-dimensional metasurface scheme capable of providing dual phase control through out-of-plane plasmonic resonance of L-shape antennas. Under circularly polarized excitation at a specific wavelength, the L-shape antennas with rotating orientation angle act as spatially variant three-dimensional tilted dipoles and are able to generate desire phase delay for different polarization components. Generalized Snell's law is achieved for both in-plane and out-of-plane dipole components through arranging such L-shape antennas into arrays. These three-dimensional metasurfaces suggest a route for wavefront modulation and a variety of nanophotonic applications.
Keywords: Physics and Astronomy (miscellaneous)

Experimental verification of the acoustic geometric phase - Liu, Bingyi; Zhou, Zhiling; Wang, Yongtian; Zentgraf, Thomas; Li, Yong; Huang, Lingling (Applied Physics Letters)
Optical geometric phase encoded by in-plane spatial orientation of microstructures has promoted the rapid development of numerous functional meta-devices. However, pushing the concept of the geometric phase toward the acoustic community still faces challenges. In this work, we utilize two acoustic nonlocal metagratings that could support a direct conversion between an acoustic plane wave and a designated vortex mode to obtain the acoustic geometric phase, in which an orbital angular momentum conversion process plays a vital role. In addition, we realize the acoustic geometric phases of different orders by merely varying the orientation angle of the acoustic nonlocal metagratings. Intriguingly, according to our developed theory, we reveal that the reflective acoustic geometric phase, which is twice the transmissive one, can be readily realized by transferring the transmitted configuration to a reflected one. Both the theoretical study and experimental measurements verify the announced transmissive and reflective acoustic geometric phases. Moreover, the reconfigurability and continuous phase modulation that covers the 2π range shown by the acoustic geometric phases provide us with the alternatives in advanced acoustic wavefront control.
Keywords: Physics and Astronomy (miscellaneous)

Tilting nondispersive bands in an empty microcavity - Gao, Ying; Li, Yao; Ma, Xuekai; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Applied Physics Letters)
Recently, microcavities with anisotropic materials were shown to be able to create bands with non-zero local Berry curvature. The anisotropic refractive index of the cavity layer is believed to be critical in opening an energy gap at the tilted Dirac points. In this work, we show that the anticrossing between a cavity mode and a Bragg mode can also be realized within an empty microcavity without any birefringent materials in the cavity layer. Nondispersive bands are observed within the energy gap due to the particular refractive index distribution of the sample. The intrinsic TE-TM splitting and XY splitting of DBR mirrors induce the squeezing of the cavity modes in momentum space, so that the nondispersive bands are tilted and spin-dependent. Our results pave the way to investigate interesting physical phenomena of photonic modes close to or in the nondispersive bands without anisotropic cavity layers.
Keywords: Physics and Astronomy (miscellaneous)

Tilting nondispersive bands in an empty microcavity - Gao, Ying; Li, Yao; Ma, Xuekai; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

High-speed hyperspectral imaging of ferroelectric domain walls using broadband coherent anti-Stokes Raman scattering - Reitzig, Sven; Hempel, Franz; Ratzenberger, Julius; Hegarty, Peter A.; Amber, Zeeshan H.; Buschbeck, Robin; Rüsing, Michael; Eng, Lukas M. (Applied Physics Letters)
Spontaneous Raman spectroscopy (SR) is a versatile method for analysis and visualization of ferroelectric crystal structures, including domain walls. Nevertheless, the necessary acquisition time makes SR impractical for in situ analysis and large scale imaging. In this work, we introduce broadband coherent anti-Stokes Raman spectroscopy (B-CARS) as a high-speed alternative to conventional Raman techniques and demonstrate its benefits for ferroelectric domain wall analysis. Using the example of poled lithium niobate, we compare the spectral output of both techniques in terms of domain wall signatures and imaging capabilities. We extract the Raman-like resonant part of the coherent anti-Stokes signal via a Kramers–Kronig-based phase retrieval algorithm and compare the raw and phase-retrieved signals to SR characteristics. Finally, we propose a mechanism for the observed domain wall signal strength that resembles a Čerenkov-like behavior, in close analogy to domain wall signatures obtained by second-harmonic generation imaging. We, thus, lay here the foundations for future investigations on other poled ferroelectric crystals using B-CARS.
Keywords: Physics and Astronomy (miscellaneous)

Optoelectronic sampling of ultrafast electric transients with single quantum dots - Widhalm, Alex; Krehs, Sebastian; Siebert, Dustin; Sharma, Nand Lal; Langer, Timo; Jonas, Björn; Reuter, Dirk; Thiede, Andreas; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
In our work, we have engineered low capacitance single quantum dot photodiodes as sensor devices for the optoelectronic sampling of ultrafast electric signals. By the Stark effect, a time-dependent electric signal is converted into a time-dependent shift of the transition energy. This shift is measured accurately by resonant ps laser spectroscopy with photocurrent detection. In our experiments, we sample the laser synchronous output pulse of an ultrafast CMOS circuit with high resolution. With our quantum dot sensor device, we were able to sample transients below 20 ps with a voltage resolution in the mV-range.
Keywords: tet_topic_qd

Two-dimensional lateral surface superlattices in GaAs heterostructures with independent control of carrier density and modulation potential - Wang, D. Q.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R.; Klochan, O. (Applied Physics Letters)

Excess noise in Al x Ga 1 − xAs/GaAs based quantum rings - Riha, Christian; Buchholz, Sven S.; Chiatti, Olivio; Wieck, Andreas D.; Reuter, Dirk; Fischer, Saskia F. (Applied Physics Letters)

Electrically controlled rapid adiabatic passage in a single quantum dot - Mukherjee, Amlan; Widhalm, Alex; Siebert, Dustin; Krehs, Sebastian; Sharma, Nandlal; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
Keywords: tet_topic_qd

Two-photon phase-sensing with single-photon detection - Vergyris, Panagiotis; Babin, Charles; Nold, Raphael; Gouzien, Elie; Herrmann, Harald; Silberhorn, Christine; Alibart, Olivier; Tanzilli, Sébastien; Kaiser, Florian (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Efficient demultiplexed single-photon source with a quantum dot coupled to a nanophotonic waveguide - Hummel, Thomas; Ouellet-Plamondon, Claudéric; Ugur, Ela; Kulkova, Irina; Lund-Hansen, Toke; Broome, Matthew A.; Uppu, Ravitej; Lodahl, Peter (Applied Physics Letters)
Planar nanostructures allow near-ideal extraction of emission from a quantum emitter embedded within, thereby realizing deterministic single-photon sources. Such a source can be transformed into M single-photon sources by implementing active temporal-to-spatial mode demultiplexing. We report on the realization of such a demultiplexed source based on a quantum dot embedded in a nanophotonic waveguide. Efficient outcoupling (>60%) from the waveguide into a single mode optical fiber is obtained with high-efficiency grating couplers. As a proof-of-concept, active demultiplexing into M = 4 spatial channels is demonstrated by the use of electro-optic modulators with an end-to-end efficiency of >81% into single-mode fibers. Overall, we demonstrate four-photon coincidence rates of >1 Hz even under nonresonant excitation of the quantum dot. The main limitation of the current source is the residual population of other exciton transitions, which corresponds to a finite preparation efficiency of the desired transition. We quantitatively extract a preparation efficiency of 15% using the second-order correlation function measurements. The experiment highlights the applicability of planar nanostructures as efficient multiphoton sources through temporal-to-spatial demultiplexing and lays out a clear path way of how to scale up toward demonstrating quantum advantages with the quantum dot sources.

Ultrafast electric phase control of a single exciton qubit - Widhalm, Alex; Mukherjee, Amlan; Krehs, Sebastian; Sharma, Nandlal; Kölling, Peter; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
We report on the coherent phase manipulation of quantum dot excitons by electric means. For our experiments, we use a low capacitance single quantum dot photodiode which is electrically controlled by a custom designed SiGe:C BiCMOS chip. The phase manipulation is performed and quantified in a Ramsey experiment, where ultrafast transient detuning of the exciton energy is performed synchronous to double pulse p/2 ps laser excitation. We are able to demonstrate electrically controlled phase manipulations with magnitudes up to 3p within 100 ps which is below the dephasing time of the quantum dot exciton.
Keywords: tet_topic_qd

Streak camera imaging of single photons at telecom wavelength - Allgaier, Markus; Ansari, Vahid; Eigner, Christof; Quiring, Viktor; Ricken, Raimund; Donohue, John Matthew; Czerniuk, Thomas; Aßmann, Marc; Bayer, Manfred; Brecht, Benjamin; Silberhorn, Christine (Applied Physics Letters)

Noble metal free photocatalytic H2 generation on black TiO2: On the influence of crystal facets vs. crystal damage - Liu, Ning; Steinrück, Hans-Georg; Osvet, Andres; Yang, Yuyun; Schmuki, Patrik (Applied Physics Letters)

Controlling the optical spin Hall effect with light - Lafont, O.; Luk, S. M. H.; Lewandowski, P.; Kwong, N. H.; Leung, P. T.; Galopin, E.; Lemaitre, A.; Tignon, J.; Schumacher, Stefan; Baudin, E.; Binder, R. (Applied Physics Letters)

Species transport on the target during high power impulse magnetron sputtering - Layes, V.; Monje, S.; Corbella, C.; Trieschmann, J.; de los Arcos de Pedro, Maria Teresa; von Keudell, A. (Applied Physics Letters)

Near infrared Kerr effect and description of field-induced phase transitions in polymer-stabilized blue phase liquid crystals - Atorf, B.; Rasouli, H.; Nordendorf, G.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Periodic domain inversion in x-cut single-crystal lithium niobate thin film - Mackwitz, P.; Rüsing, Michael; Berth, Gerhard; Widhalm, A.; Müller, K.; Zrenner, Artur (Applied Physics Letters)
We report the fabrication of periodically poled domain patterns in x-cut lithium niobate thin-film. Here, thin films on insulator have drawn particular attention due to their intrinsic waveguiding properties offering high mode confinement and smaller devices compared to in-diffused waveguides in bulk material. In contrast to z-cut thin film lithium niobate, the x-cut geometry does not require back electrodes for poling. Further, the x-cut geometry grants direct access to the largest nonlinear and electro-optical tensor element, which overall promises smaller devices. The domain inversion was realized via electric field poling utilizing deposited aluminum top electrodes on a stack of LN thin film/SiO2 layer/Bulk LN, which were patterned by optical lithography. The periodic domain inversion was verified by non-invasive confocal second harmonic microscopy. Our results show domain patterns in accordance to the electrode mask layout. The second harmonic signatures can be interpreted in terms of spatially, overlapping domain filaments which start their growth on the þz side.

Ultrafast carrier dynamics and resonant inter-miniband nonlinearity of a cubic GaN/AlN superlattice - Jostmeier, Thorben; Wecker, Tobias; Reuter, Dirk; As, Donat Josef; Betz, Markus (Applied Physics Letters)

Fabrication and characterisation of gallium arsenide ambipolar quantum point contacts - Chen, J. C. H.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Trunov, K.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)